(untitled) (MATEMATIKA, 2009)
Foreign exchange rate factor give the big impact to the international firms because of the floating of Ringgit Malaysia currency influenced by the volatility of other foreign currencies. Malaysian firm equity return drop cause by devaluation of Ringgit Malaysia. This study suggested the fuzzy criterion to derive the risk measurement and estimates the exchange rate robustness implied by the comparison of exchange rate changes for twenty-four months. Keywords: Fuzzy criterion; fuzzy interval; foreign exchange risk; exchange rate robustness